Health information management technology : an applied approach - Sayles, Nanette B.; Gordon, Leslie L.; American Health Information Management Association (Chicago, Illinois : American Health Information Management Association, 2016)
"Creates a blueprint for success in the health information management (HIM) field. Chapter content is expanded in the fifth edition to prepare students for transitional and changing roles in an electronic health information environment. All chapters are updated to reflect current HIM trends, practices, standards, and legal issues. Written by distinguished leaders in the field, this book guides students through two-year academic programs in preparation for the Registered Health Information Technician (RHIT) certification exam and beyond"--
Part I: Foundational Concepts. Health information management profession -- Healthcare delivery systems -- Health information functions, purpose, and users -- Part II: Data Content Structures and Standards. Health record content and documentation -- Clinical terminologies, classifications, and code systems -- Data management -- Secondary data sources -- Part III: Information Protection: Access, Disclosure, and Archival Policy and Security. Health law -- Data privacy and confidentiality -- Data security -- Part IV: Informatics, Analytics, and Data Use. Health information technologies -- Healthcare information -- Research and data analysis -- Healthcare statistics -- Part V: Revenue Management and Compliance. Revenue management and reimbursement -- Fraud and abuse compliance -- Part VI: Leadership. Leadership -- Performance improvement -- Management -- Human resources management and professional development -- Ethical issues in health information management.
"AHIMA product no. AB103115"--Title page verso.
Includes bibliographical references and index.
Keywords: Medical informatics; Information resources management; Medicine -- Information technology; Delivery of Health Care -- organization & administration; Information Management -- organization & administration; Forms and Records Control; Medical Informatics; Medicine -- Information technology; Information resources management; Medical informatics